Regional Economy Competitiveness as a Determinant of the Human Capital Level of Exemplified by the Warmińsko-Mazurskie Voivodeship - Merło, Paweł; Bogdański, Marcin (Olsztyn Economic Journal, 2017)
The Warmińsko-Mazurskie Voivodeship belongs to the group of voivodeships with a low level of economic growth in Poland. When considering the importance of human capital in the process of economic growth stimulation, it should be emphasised that the low level of human capital is one of the obstacles preventing the acceleration of economic growth and improvement in the region. The purpose of the presented analyses was to find the reasons for the low level of human capital in the Warmińsko-Mazurskie Voivodeship. The results, prove that the level of human capital in the regions of Warmia, Mazury and Powiśle results from low competitiveness as regards to higher education, and the low competitiveness potential of the regional economy. In a consequence, the labor market is in an unfavorable situation which leads to the outflow of the most skilled and best-educated parts of the labor force.